Tuberculosis Profile in Chile: Effect of Migration, Overcrowding and Income on Tuberculosis and Its Spatial Distribution - Vargas-Rona, C; Elorrieta-Lopez, F; Maddaleno-Herrera, M (SOC MEDICA SANTIAGO, 2024)
Aim: To analyze tuberculosis (TB) incidence, demographic profiles, and associated risk factors in migrant and national populations, in order to understand the impact of migration, overcrowding, and socioeconomic factors on TB prevalence and care-seeking behaviors. Material and Methods: Data from various communes within the Metropolitan Region and other parts of the national territory were analyzed to assess TB incidence, demographic characteristics, and care-seeking behaviors among migrant and national populations. Results: TB disproportionately affects males in both migrant and national populations. Migrants exhibit a younger demographic profile, higher proportion of HIV coinfection. Migration and overcrowding positively influence the Risk of Morbidity from TB (RME) in specific communes, whereas socioeconomic income negatively impacts the RME, being the most relevant explanatory factor. Conclusions: TB remains a significant public health challenge influenced by migration, overcrowding, and socio-economic disparities. Tailored interventions focusing on high-risk groups and specific geographic areas are essential for effective control strategies. Future research should explore the impact of the COVID-19 pandemic on TB dynamics and associated socio-health factors.